Impact of Workload and Work Environment on Employee Performance: A Study at PT. Samira Makmur Sejahtera - Safitri, Husnaina Mailisa; Sulfitra; Yukriani (Journal of Principles Management and Business, 2025)
This study aims to analyze the effect of workload and work environment on employee performance, with work stress as a mediating variable at PT. Samira Makmur Sejahtera. The research employs a quantitative approach with simple random sampling, involving 91 employees as samples. Data were analyzed using path analysis along with outer and inner model analysis, assisted by SmartPLS 4.1.0.5 software. The results indicate that workload has a positive and significant effect on employee performance, as does the work environment. Workload also positively and significantly affects work stress, while the work environment has a negative and significant effect on work stress. Work stress negatively and significantly affects employee performance. Mediation analysis reveals that work stress mediates the effect of the work environment on performance, but not the effect of workload. These findings highlight the importance of managing a conducive work environment to enhance employee performance and reduce work stress at PT. Samira Makmur Sejahtera.